Representation of Indigenous Nationalities and Minorities in Bank and Financial Institutions: A Study of Pokhara - Gurung, Jas Bahadur (Himalayan Journal of Sociology and Anthropology, 2014)
This study is carried out to explore the inclusive representation of Indigenous Nationalities and Minorities working in Bank and Financial Institutions (BFIs) in Pokhara. Both descriptive and explorative research design has been used in this study. Primary data have been collected constructing a set of well-structured questionnaire and used in this study. Representation of Indigenous Nationalities is poor i.e. only 32.59 percent in the total employment of BFIs. Madheshi represents only 0.62 percent and Dalits 1.62 percent in the total employment. There is no representation at all from Muslim community in BFIs in Pokhara. The representation of male employee is higher than that of female employees in BFIs even within the said ethnic groups. The level of job they employed is mostly lower levels i.e. assistants and other support staffs. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10688 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 51-63